Strategic Interaction Across Countries and Multinational Agglomeration: An Application to the Cement Industry - Ghemawat, Pankaj; Thomas, Catherine (Management Science, 2008)
Agglomeration in foreign direct investment (FDI) is typically attributed to location-specific characteristics such as natural resource advantages or production-related spillovers between multinational firms. The increasing collocation of the largest global firms in the cement industry since the 1980s is not easily attributed to either of these explanations. This paper draws on theories of multimarket contact to test whether strategic interaction across national markets has influenced the successive market entry decisions generating the observed agglomeration. We first establish that there is indeed nonrandom agglomeration of the six largest cement firms. We next show that preexisting cross-market interaction with current incumbents helps predict which firm will enter a given market and also the choice of market a given firm enters. The association does not appear to be caused by strategic convergence or mimicry of recent entry events and cannot be explained by production side effects, which depend only on local conditions. The findings are consistent with multimarket contact models where collocation allows firms to sustain higher prices in all markets. This latter inference is also supported by evidence of an association between global firm market share and local cement price. The paper suggests that pricing spillovers can serve as an alternative motivation for FDI agglomeration.